A contribuição de marketing para a geração e apropriação de valor para o acionista: um estudo na indústria de franchising - Souza, Ricardo Fasti de (2001)
Transactions are relevant focal units to provide assessment to several marketing situations. It is relevant for the present study to describe, explain and foreseeing the shareholder value appropriation process on a dyadic transactional structure. The process description is developed based upon the following theoretical blocks: transaction costs economics; comparative advantage theory; competitive advantage theory; agency theory and quasi-rent. It is worth noting the attempt to integrate marketing and economics concepts, mainly related to the rent flow appropriation due to marketing processes. The explanation is based upon the author's model proposition which engulfs value creation sources, power sources and degree of dependence as constructs that contribute to the enlighten of value appropriation oh transactions. The foreseeing is developed trough an econometric application of the recommended model in the Brazilian franchising industry in 2000. The dependent variable is a ratio between the franchise fee ant the investment necessary for opening a new unity as a proxy to the cash flow appropriation capabilities of the franchise fee, since the theoretical assumption is that the more the investment leverages the revenues the greater the franchise fee. The independent variables are value creation sources operators. Power sources and dependence degree were held constant due to the contractual nature of the industry. Results suggest that market based assets have impact on the rents appropriation capabilities, here represented by the franchise fee. The model reinforces the importance of marketing role and contribution to the appropriation of shareholder value.